The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1634/theoncologist.12-5-565
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: IMRT for Head and Neck Cancer: Many Chapters Left to Write

Abstract: Disclosure of potential conflicts of interest is found at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The radiation-induced toxicities were endurable. Recent studies have demonstrated that target volume coverage and critical organ protection were significantly improved with intensity-modulated radiotherapy (IMRT) compared with 3D-CRT in head-and-neck malignant tumor (13,14). It is reasonable for us to hypothesize that the higher dose could be given to involved regions and that OS might be improved by IMRT.…”
Section: Discussionmentioning
confidence: 99%
“…The radiation-induced toxicities were endurable. Recent studies have demonstrated that target volume coverage and critical organ protection were significantly improved with intensity-modulated radiotherapy (IMRT) compared with 3D-CRT in head-and-neck malignant tumor (13,14). It is reasonable for us to hypothesize that the higher dose could be given to involved regions and that OS might be improved by IMRT.…”
Section: Discussionmentioning
confidence: 99%
“…When concurrent chemoradiation is used, there is further variation over the choice of optimum fractionation schedule. IMRT, with its potential for Simultaneous Integrated Boost (SIB), further adds to this uncertainty [1] such that there is an increasing lack of uniformity of practice with no single 'standard of care'.…”
mentioning
confidence: 99%